ZOOPLANKTON DIVERSITY IN THE RIVER JALDHAKA, WEST BENGAL, INDIA - SARKAR, TAPAN; PAL, JOYDEB (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
A survey was carried out on the zooplankton diversity at two sampling sites in the river Jaldhaka from March 2014 to February 2016. A total 16 zooplankton genera belonged to Protozoa (5 genera, 31%), Rotifera (5 genera, 31%), Copepod (3 genera, 19%) and Cladocera with 3 genera (19%) were recorded. Density, number of phytoplankton genera, Shannon diversity index, evenness index, Margalef’s richness index and dominance index ranged with mean value were 8-27 (16.48), 6-13 (10.02), 1.73-2.51(2.22), 0.903-0.99 (0.964) and 2.27-4.23 (3.24) respectively. Presence of rotifers Brachionus, Filinia, and Polyarthra are indications of slightly eutrophic conditions of the river water. The objectives of the study assess the zooplankton diversity and contamination status of the River Jaldhaka.